The Impact of Transformational Leadership Style and Employee Development on Performance Effectiveness - Kosasih Kosasih; Bona Ventura Feber Freitas; Uliana Nur Melin; Retno Arienta Sari; Ester Krisdayanti (Business and Applied Management Journal, 2025)
The purpose of this research is to analyze factors influencing employee performance. The factors include identifying the impact of transformational leadership style and employee development on performance effectiveness. This research employed a quantitative method with regression analysis. Data were collected through an online questionnaire distributed to employees. The research population consisted of 89 employees, and the sample was saturated (census). Data were analyzed using IBM SPSS version 26 and tested for validity, reliability, classical assumptions, multiple linear regression, and coefficient of determination. The results indicate that both transformational leadership style and employee development, both partially and simultaneously, have a positive and significant effect on employee performance effectiveness. The better the transformational leadership style and employee development, the more effective the employee performance.